Literary theory and criticism : recent writings from South Asia - Gupto, Arun. (New York : Routledge, 2022)
"The book explores key South Asian writings on cultural theory and literary criticism. It discusses the dynamics of textual contents, rhetorical styles, and socio-political issues through an exploration of seminal South Asian scholarship in the Humanities and Social Sciences. The volume examines concepts and methods of critical studies. It also discusses colonial and postcolonial discourses on art, religion, nationalism, identity, representation, resistance, and gender in the South Asian context. The essays are accompanied by textual questions and intertextual discussions on rhetorical, creative, and critical aspects of the selected texts. The exercise questions invite the reader to explore the mechanics of reading about and writing on discursive pieces in South Asian studies. Comprehensive and interdisciplinary, this textbook will be indispensable for students and researchers of South Asian studies, cultural theory, literary criticism, postcolonial studies, literary and language studies, women and gender studies, rhetoric and composition, political sociology, and cultural studies"
English
Keywords: Literature -- History and criticism -- Theory